Some characteristics of growth process of longarm mullet (Mugil kelaartii Gunther, 1861) fish in O Loan lagoon, Phu Yen province - Phi Loan, Nguyen Thi; Phu, Vo Van; Tang, Vu Trung (Academia Journal of Biology, 2012)
Longarm mullet (Mugil kelaartii) fish in lagoons O Loan, Phu Yen province is a kind of economic species and people can catch them with big production. This fish is a speciality of the locality due to its sweet-smelling and tastiness. At present, aquatic resource in lagoons and inshore zone of Phu Yen province is over-exploiting by destructive means that causes serious declining of Longarm mullet population. This article presents results of au thors’ research on some characteristics of growth of Longarm mullet species. Theresults can be used in buiding a pattern of aquaculture farming of Longarm mullet. Longarm mullet (Mugil kelaartii) has a high economic value at O Loan Lagoon, Phu Yen Province has a high economic value at O Loan Lagoon, Phu Yen Province. In the months of the 3 years, from January 2007 to December 2009, we collected 1,154 individuals of Longarm mullet fish population at O Loan lagoon. Fish has a average size and length is about 184 mm with the weight is 130.0 g. To the premature, it increases the length, in contrast the mature increases the weight quickly. The age structure of Longarm mullet fish is simple, including 4 groups of age. Fish has the biggest size which is about 220 mm, correlatived to 245.4 g. Fish which have the size of 18mm shall begin to form scales. In O Loan Lagoon, those Longarm mullet (Mugil kelaartii) fish is exploited with a small scale compared to the Mugil kelaartii fish population at the coastal water, so the value of business as well as food is not high enough. As a result, the exploitation must be ruled properly. At the same time, doing research on biology and reproduction should be interested to hold the initiative in the breed to raise this kind of fish.